IoT and Arduino Based Design of a Solar, Automated and Smart Greenhouse for Vegetable - Nouadjep Serge Narcisse; Djouodjinang Husserl Fonou (E3S Web of Conferences, 2022)
Seasonal farming practiced in Cameroon is a major limitation to our gross domestic product. In this context, introduction of a standalone solar, automated and smart greenhouse system to improve agricultural yield in quality and quantity could provide a solution for all year round crop production while minimizing the total power demand for industrial, mechanical, chemical and commercial uses. This system comes to solve the problem of too much reliance on seasonal climatic conditions by increasing our total crops produced and reducing the amount of farmland exploited as well as environment preservation. Regulated automatically, proposed solution incorporates several modules including: a solar power system and all the physicochemical parameters (room temperature, room humidity, light intensity, amount of CO2, pH, soil humidity, amount of nitrogen, phosphorous and potassium) necessary for good production of vegetables in quantities and qualities regardless of the weather. The electronic modules were designed and realized based on Arduino and Internet of Things (IoT). Using a Wi-Fi module and a Geogebra software, an android application was developed for monitoring, displaying, and analyzing those parameters. This enables the control of all aforementioned components of the greenhouse system from any device capable of using Wi-Fi regardless, of the distance of the operator. A mathematical correlation were established between the voltage and various physicochemical parameters. With a daily consumption of 653Wh, the overall system has an efficiency of 65% with a peak power of 400W.